The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00232-008-9150-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Drug Responses on Native GABAA Receptors Revealing Heterogeneity in Extrasynaptic Populations in Cultured Hippocampal Neurons

Abstract: Hippocampal pyramidal neurons potentially express multiple subtypes of GABA(A) receptors at extrasynaptic locations that could therefore respond to different drugs. We activated extrasynaptic GABA(A) receptors in cultured rat hippocampal pyramidal neurons and measured single-channel currents in order to compare the actions of two drugs that potentially target different GABA(A) receptor subtypes. Despite the possible difference in receptor targets of etomidate and diazepam, the two drugs were similar in their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Diazepam potentiation of the GABA current causes an increase in open probability; when the conductance is low (Ͻ40 pS), this is often accompanied by an increase in single-channel conductance (1,5). In the example shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Diazepam potentiation of the GABA current causes an increase in open probability; when the conductance is low (Ͻ40 pS), this is often accompanied by an increase in single-channel conductance (1,5). In the example shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The ability of 2′MeO6MF to directly activate native GABA A channels was examined in hippocampal neurons from the newborn rat. Pharmacological (Caraiscos et al ., 2004; Mangan et al ., 2005; Herd et al ., 2008; Seymour et al ., 2009) and competitor peptide experiments have shown that these neurons express multiple receptor subtypes including γ‐ and δ‐containing GABA A channels. Single‐channel currents in response to 2′MeO6MF were recorded from inside‐out patches pulled from cultured neurons and their characteristics compared with those observed with GABA.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we examined the actions of an analogue of 6‐methylflavone, 2′methoxy‐6‐methylflavone (2′MeO6MF) on human recombinant α1–3,5β1–3γ2L and α1/2β2 GABA A receptors expressed in Xenopus oocytes and on native GABA A receptors in rat newborn hippocampal patches that express multiple receptor subtypes (Seymour et al ., 2009). In this study, we report that 2′MeO6MF positively modulates α1β1–3γ2L GABA A receptors, whereas at α2β2/3γ2L GABA A receptors, the flavonoid directly activates these receptors in the absence of GABA.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological studies demonstrated that a clinically relevant concentration etomidate either enhanced the amplitude of GABA-evoked Cl -currents or increased the GABAergic inhibitory transmission [1][2][3][4][5]. In cultured hippocampal neurons, etomidate potentiated GABA-evoked currents by increasing the open probability, conductance and the open time of single channel [6,7]. In mammalian cerebellar cortex, MILs provide dendritic and somatic inhibition of PCs through the activation of GABA A receptors, indicating that GABA A receptors activity play a critical role in regulation of PCs activity [22].…”
Section: Etomidate Facilitates Gabaergic Transmissionmentioning
confidence: 99%
“…Electrophysiological studies showed that etomidate either enhanced the amplitude of Cl -currents evoked by application of GABA, or increased GABAergic inhibitory transmission [1][2][3][4][5]. At a clinically relevant concentration of etomidate, potentiated GABA currents resulted in increases in open probability, membrane conductance and the open time of single GABA channel in cultured hippocampal neurons [6,7]. In rat spinal dorsal horn neurons, the etomidate actions were concentration-dependent: etomidate at 10 μmol\L potentiated GABA-activated current, slowed activation, desensitization and deactivation of GABA A receptors; etomidate at 10-1,000 μmol\L directly activated and desensitized GABA A receptors [1].…”
Section: Introductionmentioning
confidence: 99%